Social Media and Self-Harm: A Study on Its Perception Among University Students in Spain - Martínez-`Pastor, Esther; Blanco-Ruíz, Marian; Nicolás-Ojeda, Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The rise of non-suicidal self-injury (NSSI) among young people has intensified debate on the role of social media as spaces for information, socialization, and mental health risks. This study examines the perceptions of university students in Spain regarding NSSI and the need for digital content regulation. A survey of 1,011 participants revealed that 31% identified social media as their main source of information on self-harm, 11% had searched for content on Twitter (30%) and TikTok (30%), and 95% supported stronger regulation to prevent its dissemination, highlighting the ambivalent role of platforms between support and risk.